Predicting Future Deterioration of Hydraulic Steel Structures with Markov Chain and Multivariate Samples of Statistical Distributions - Guillermo A. Riveros; Elias Arredondo (Journal of Applied Mathematics)
Combined effects of several complex phenomena cause the deterioration of elements of steel hydraulic structures on the nation’s lock systems: loss of protective systems, corrosion, cracking and fatigue, impacts, and overloads. This paper presents examples of deterioration of steel hydraulic structures. A method for predicting future deterioration based on current conditions is also presented. This paper also includes a procedure for developing deterioration curves when condition state data is available.